Human Factors Affecting the Application of Information Technology by TUMS Middle Managers in 2010 - H Barzekar; M Eshraghian; H Dargahi; R Safdari (Tehran University of Medical Sciences, 2011)
Background and Aim: One of the most important reasons why organizations are distinguished from one another is the degree of application and implementation of information technology in their organizational activities. In this regard, individual factors contribute considerably to the application of information technology (IT). Such factors include employees' perceptions and attitudes towards information technology and their demographic characteristics which affect the level of information technology acceptance and implementation.Materials and Methods: In this cross-sectional study, 110 middle managers from teaching hospitals of Tehran University of Medical Sciences (TUMS) were chosen. A structured questionnaire was used as the data collection device and its validity and reliability were confirmed by a pilot study.Results: Of the participants, 62.9% were males and 37.1% were females. The findings show that there is a statistically significant relationship between perception and making decisions based on the implementation of information technology. However, there was no significant relationship between work experience, education and training on the one hand and IT implementation on the other.Conclusion: The results show that human factors (perception and decision) have a considerable impact on the implementation of information technology. Top managers and experts should consider the important aspects of human factors and also the factors affecting them.